Working for the world : the evolution of Australian Volunteers International - Britton, Peter, M.A. (North Melbourne, Vic : Australian Scholarly Publishing, 2019)
Since 1951 thousands of volunteers from all over Australia have worked in developing countries across the world. This is the story of the organisation that made this possible, the Overseas Service Bureau later known as Australian Volunteers International. From its origins as a community-based association expressing solidarity with people in newly independent countries, it grew into a significant organisation managing a suite of international development programs. The organisation’s activist impulses and principles were evident as it responded to the critical international issues of the times. It supported opponents of apartheid in Southern Africa, worked in Cambodia when Australia had no diplomatic representation there and in Vietnam when Australian aid had been suspended, nurtured relationships with Indonesian NGOs during Suharto’s reign, supported civil society across the Pacific Islands, and provided significant and timely support for East Timor’s self-determination. This book explores the organisation’s growth with increased government funding and the accompanying challenge of maintaining its own values and identity in an era when decolonisation presented increasingly complex demands.
Includes bibliographical references (pages 266-288) and index.
Keywords: Australian Volunteers International; Overseas Service Bureau (Australia).; Volunteer Graduate Scheme (Australia).; Volunteers -- Developing countries; Voluntarism -- Developing countries; Volunteer workers in social service; Technical assistance, Australian; International cooperation; Australian